Improved eating and cooking quality of indica rice cultivar YK17 via adenine base editing of Wx(a) allele of Granule-Bound Starch Synthase I (GBSS I) - Monsur, Mahmuda Binte; Ni, Cao; Xiangjin, Wei; Lihong, Xie; Guiai, Jiao; Tang, Shaoqing; Sreenivasulu, Nese; Gaoneng, Shao; Peisong, Hu (Elsevier, 2021)
Amylose content (AC) is the key determinant of eating and cooking quality (ECQ) of rice. The major Wxa allele of granule-bound starch synthase I (GBSS I) in indica rice produces higher AC, making rice hard and dry after cooking. Recent work has improved ECQ of japonica rice via clustered regularly interspaced short palindromic repeats/CRISPR- associated protein 9 (CRISPR/Cas9) or cytosine base editing (CBE) techniques. However, base editing has not yet been applied to modify the Wxa allele of indica rice. We utilized a novel precise adenine base editing (ABE) tool to generate three mutants of indica cultivar Zhongjiazao 17 (YK17) with reduced AC while other ECQ parameters, such as gel consistency (GC) and alkali spreading value, were maintained. Our study demonstrated improvement of ECQ of indica rice and will help rice breeders satisfy consumers.